2021
DOI: 10.1007/s41979-021-00053-3
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Student STEM Learning: Self-Efficacy and Outcome Expectancy, 21st Century Skills, and Career Awareness

Abstract: Social, motivational, and instructional factors impact students’ outcomes in STEM learning and their career paths. Based on prior research and expectancy-value theory, the study further explored how multiple factors affect students in the context of integrated STEM learning. High school STEM teachers participated in summer professional development and taught integrated STEM to students during the following school year, where scientific inquiry, biomimicry, 3D printing technology, and engineering design were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 55 publications
1
47
0
3
Order By: Relevance
“…Besides the above results, our research elaborates the theoretical framework, such as project theme selection, student work, and multi-evaluation algorithm. However, we still find that individual students have learning burnout because the differences in students' self-efficacy affect their initiative to participate in learning [22]. Improving courses' quality to encourage students to participate in education activities is often inefficient [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides the above results, our research elaborates the theoretical framework, such as project theme selection, student work, and multi-evaluation algorithm. However, we still find that individual students have learning burnout because the differences in students' self-efficacy affect their initiative to participate in learning [22]. Improving courses' quality to encourage students to participate in education activities is often inefficient [15].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the learning environment can affect students' attitudes. Especially the self-efficacy and learning motivation can also affect future career planning [22].…”
Section: Research Statusmentioning
confidence: 99%
“…It has been reported that students' positive attitude towards STEM has a significant impact on the realization of STEM education objectives and 21st century learning skills acquisition (Luo et al, 2019;Mahoney, 2010;Tseng et al, 2013). For STEM attitude, the existing research mainly focuses on its effect on learning effectiveness (Han et al, 2021), or concentrates on the comparison of differences in STEM attitude (Zhou et al, 2019). The other research also concentrates on the functional description of the effect of STEM attitude on 21st century learning skills learning (Akcanca, 2020).…”
Section: Factors Influencing 21st Century Learning Skillsmentioning
confidence: 99%
“…Research verifies high-order thinking skills (HOTS) is such an ability to apply skills, knowledge, and values in reasoning that can be used in the STEM field and may influence careers later (Lin, et al, 2018). The self-efficacy and learning motivation can also affect future career planning (Han, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%